Myxosporea (Cnidaria : Myxozoa) infecting the saddled seabream Oblada melanura (L. 1758) (Teleostei : Sparidae) and the painted comber Serranus scriba (L. 1758) (Teleostei : Serranidae) in Tunisia - Laamiri, Sayef (Zootaxa, 2017)
First parasitological surveys of Myxozoa are performed on the sparid saddled seabream Oblada melanura (Linnaeus, 1758) and the serranid painted comber Serranus scriba (Linnaeus, 1758) caught from the Bay of Bizerte and the Gulf of Tunis respectively in Northeast Tunisia, Western Mediterranean. In this study, 6 bivalvulid myxosporean species belonging to the 3 genera Ceratomyxa Thélohan, 1892, Myxodavisia Zhao, Zhou, Kent & Whipps, 2008 and Zschokkella Auerbach, 1910, are isolated infecting their hosts. Two species Ceratomyxa sp. 1 ex O. melanura (Prevalence (P) = 36%) and Ceratomyxa sp. 2 ex O. melanura (P = 13%) infected the saddled seabream and four species Ceratomyxa sp. 1 ex S. scriba (P = 11.7%), Ceratomyxa sp. 2 ex S. scriba (P = 6.7%), Myxodavisia sp. (P = 8.3%) and Zschokkella sp. (P = 5.6%) infected the painted comber. These myxosporeans differ, in vegetative stages and/or in mature spores, from all the previously known congeneric species, and are described here on the basis of their morphological and morphometric features, their host and tissue specificities and their biogeographical distribution. This is the first report of myxosporean infections in O. melanura and S. scriba. The occurrence of two ceratomyxid species in each host species supports that the genus Ceratomyxa is host-specific not only in sparids but also in serranids, which agrees with data previously obtained from Sparidae in Mediterranean Sea and from Serranidae in GBR, Australia. A member of the myxosporean genus Myxodavisia is recorded from the Mediterranean Sea for the first time, and Zschokkella spp. infections have not previously been recorded from a host in Serranidae. During the examination, a several cases of Co-infection among myxosporeans, both with two and three species, are provided and statistically studied. Indeed, 5% of the breams and 9.4% of the combers are infected with more than one myxosporean parasite. The relationship between myxosporean infections and some biological parameters are pointed out. A higher prevalence of myxosporean infection is coincided with the peak period of spawning activity in May-June for S. scriba. For both hosts, analysis using Fulton’s condition factor (K) has revealed no significant difference between infected and non-infected fishes. Clinically, no external signs of disease have been occurred in infected hosts, but some changes in the bile fluid, colour, and viscosity and in the gall bladder ’s tissue are examined in S. scriba.